Analysis of permeability and biological properties of dentin treated with experimental bioactive glasses - Reis, Bruna de Oliveira [UNESP]; Prakki, Anuradha; Stavroullakis, Alexander Terry; Souza, Marina Trevelin; Siqueira, Renato Luiz; Zanotto, Edgar Dutra; Briso, André Luiz Fraga [UNESP]; Tavares Ângelo Cintra, Luciano [UNESP]; Henrique dos Santos, Paulo [UNESP] (My University, 2021)
Objectives: To evaluate obliterating capability and biological performance of desensitizing agents. Methods: 50 dentin blocks were distributed according to the desensitizing agent used (n = 10): Control (Artificial saliva); Ultra EZ (Ultradent); Desensibilize Nano P (FGM); T5-OH Bioactive Glass (Experimental solution); F18 Bioactive Glass (Experimental solution). Desensitizing treatments were performed for 15 days. In addition, specimens were subjected to acid challenge to simulate oral environment demineralizing conditions. Samples were subjected to permeability analysis before and after desensitizing procedures and acid challenge. Cytotoxicity analysis was performed by using Alamar Blue assay and complemented by total protein quantification by Pierce Bicinchoninic Acid assay at 15 min, 24-h and 48-h time points. Scanning electron microscopy and energy dispersion X-ray spectroscopy were performed for qualitative analysis. Data of dentin permeability was analyzed by two-way repeated measures ANOVA and Tukey's test. For cytotoxicity, Kruskal-Wallis and Newman-Keuls tests. Results: for dentin permeability there was no significant difference among desensitizing agents after treatment, but control group presented highest values (0.131 ± 0.076 Lp). After acid challenge, control group maintained highest values (0.044 ± 0.014 Lp) with significant difference to other groups, except for Desensibilize Nano P (0.037 ± 0.019 Lp). For cytotoxicity, there were no significant differences among groups. Conclusion: Bioglass-based desensitizers caused similar effects to commercially available products, regarding permeability and dentin biological properties. Clinical significance: There is no gold standard protocol for dentin sensitivity. The study of novel desensitizing agents that can obliterate dentinal tubules in a faster-acting and long-lasting way may help meet this clinical need.
Keywords: Cell biology; Dentin permeability; Dentin sensitivity; Desensitizing agents